Expression of p16 and p21 in the frontal association cortex of ALS/MND brains suggests neuronal cell cycle dysregulation and astrocyte senescence in early stages of the disease. (17th June 2019) - Vazquez‐Villaseñor, I.; Garwood, C. J.; Heath, P. R.; Simpson, J. E.; Ince, P. G.; Wharton, S. B.
Abstract : Aims: Cellular senescence plays a role in organismal ageing and has been linked to persistent DNA damage in age‐related diseases. Brain senescence has been described in astrocytes and microglia, but it is less well understood in neurones. Evidence suggests that neurones activate a senescence‐like mechanism that could contribute to neurodegeneration. We aimed to determine whether a persistent DNA damage response (DDR) and senescence activation are features of motor neurone disease (amyotrophic lateral sclerosis, ALS/MND). Methods: We examined expression of senescence (p16 and p21) and DNA damage markers (8‐OHdG and γH2AX) in motor cortex (MCx), frontal association cortex (FACx) and occipital cortex (OCx) in post‐mortem tissue donated by patients with ALS/MND and controls. Results: Nuclear expression of p16 and p21 was detected in glial cells; double immunofluorescence for p16/p21 and glial fibrillary acidic protein (GFAP) suggested that some of these cells were GFAP + astrocytes. p21 nuclear expression was also found in neurones. Higher levels of p16 + (glia, P = 0.028 ) and p21 + (glia, P = 0.003 ; neurones, P = 0.008 ) cells were found in the FACx of ALS/MND donors but not in the MCx or OCx. Expression of p16 and p21 did not correlate with 8‐OHdG or γH2AX. Conclusions: Expression of p16 and p21 in glia, mainly in astrocytes, suggests senescence induction in these cells; however, neuronal p21 expression might reflect a more general mechanism of age‐related cell cycle dysregulation. The significantly higher proportion of cells expressing either p16 or p21 in the FACx of ALS/MND donors could indicate senescence activation and cell cycle dysregulation in early stages of the disease.